Comparative efficacy of second-generation androgen receptor inhibitors for treating prostate cancer: A systematic review and network meta-analysis - Chen, Xiangyu; Wang, Qihua; Pan, Yang; Wang, Shangren; Li, Yuezheng; Zhang, Hao; Xu, Mingming; Zhou, Hang; Liu, Xiaoqiang (Frontiers in Endocrinology, 2023)
Introduction: Second-generation androgen receptor inhibitors (SGARIs), namely enzalutamide, apalutamide, and darolutamide, are good for improving survival outcomes in prostate cancer patients, but some researchers have shown that using SGARIs increases side effects, which complicates clinicians' choice of. Therefore, we performed this network meta-analysis to assess the efficacy and toxicity of several SGARIs in the treatment of patients with metastatic hormone-sensitive prostate cancer (mHSPC), non-metastatic castration-resistant prostate cancer (nmCRPC), and metastatic castration-resistant prostate cancer (mCRPC). Methods: We searched PubMed, EMBASE and Cochrane Library databases from January 2000 to December 2022 to identify randomized controlled studies associated with SGARIs. We use Stata 16.0 and R 4.4.2 for data analysis, hazard ratio (HR) with 95% confidence intervals (CI) were used to assess the results. Results: This meta-analysis included 7 studies with a total of 9488 patients. In mHSPC, enzalutamide and darolutamide had a positive effect on overall survival (OS) (HR, 0.70; 95% CI, 0.59-0.82), but we did not find a difference in their efficacy to improve OS (HR, 1.19; 95% CI, 0.75-1.89). Also in nmCRPC, enzalutamide, apalutamide and darolutamide were beneficial for metastasis-free survival (MFS) (HR, 0.32; 95% CI, 0.25-0.41). Compared to darolutamide, enzalutamide (HR, 0.71; 95% CI, 0.54-0.93) and apalutamide (HR, 0.68; 95% CI, 0.51-0.91) prolonged MFS, but there was no difference in efficacy between enzalutamide and apalutamide (HR, 0.97; 95% CI, 0.73-1.28). Finally in mCRPC, there was no significant difference in indirect effects on OS between pre- and post-chemotherapy enzalutamide (HR, 0.89; 95% CI, 0.70-1.13). However, using enzalutamide before chemotherapy to improve radiographic progression-free survival (rPFS) was a better option (HR, 2.11; 95% CI, 1.62-2.73). Conclusion: The SGARIs used in each trial were beneficial for the primary endpoint in the study. Firstly there was no significant difference in the effect of enzalutamide and darolutamide in improving OS in patients with mHSPC. Secondly improving MFS in patients with nmCRPC was best achieved with enzalutamide and apalutamide. In addition both pre- and post-chemotherapy use of enzalutamide was beneficial for OS in mCRPC patients, but for improving rPFS pre-chemotherapy use of enzalutamide should be preferred.